Evaluating mental health facilitation in Brunei’s higher education: Student perspectives - Rahim, Atif; Yueh, Lee Kok; Salleh, Shana Mat; Mumin, Mas Ayu; Ibrahim, Fahmi; Padilla-Valdez, Nena (Edelweiss Applied Science and Technology, 2025)
This study evaluates the mental health facilitation techniques employed by higher education institutions in Brunei Darussalam, focusing on student experiences during the COVID-19 pandemic. The purpose of the study is to assess the effectiveness of institutional strategies supporting student well-being and to identify barriers students face in accessing mental health services. A mixed-method design was adopted; quantitative data were collected from 82 undergraduate students via an online survey, while qualitative data were gathered through in-depth interviews with 10 students who met specific inclusion criteria. The findings highlight significant psychological challenges, including stress, anxiety, and emotional fatigue, particularly linked to online learning and social isolation. Moreover, students reported several barriers, such as stigma, lack of awareness, limited access to resources, and confidentiality concerns, which hindered help-seeking behaviors. The study concludes that while institutions provide support, the outreach, accessibility, and cultural sensitivity of these services remain limited. Practical implications include the need for student-centered mental health frameworks, improved resource dissemination, and stigma reduction initiatives. Educational institutions should prioritize proactive and inclusive strategies to enhance mental well-being in alignment with national and global health policies.